2009
DOI: 10.1111/j.1349-7006.2009.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy smoking history interacts with chemoradiotherapy for esophageal cancer prognosis: A retrospective study

Abstract: Smoking is a well-known risk factor for esophageal cancer. However, there are few reports that directly evaluate smoking as a prognostic factor for esophageal cancer. Moreover, scarce evidence is available on whether smoking interacts with major treatment modalities of esophageal cancer. In this study we retrospectively analyzed 364 patients with esophageal squamous cell cancer who were treated between 2001 and 2005 at our institution. Background characteristics, including smoking history, were analyzed as pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 18 publications
4
74
0
Order By: Relevance
“…The other factor was cigarette smoking which inversely predicted the survival. This is consistent with several studies (Sundelof et al, 2008;Cescon et al, 2009;Shitara et al, 2010). Female patients had a tendency to a better survival rate during time, but this difference did not reach the significance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The other factor was cigarette smoking which inversely predicted the survival. This is consistent with several studies (Sundelof et al, 2008;Cescon et al, 2009;Shitara et al, 2010). Female patients had a tendency to a better survival rate during time, but this difference did not reach the significance.…”
Section: Discussionsupporting
confidence: 92%
“…This is reflected in the 1 and 3 year survival rates as well.Survival of esophageal cancer is influenced by several factors. Age of patients was one of the Predictive factors in the current study and was inversely associated with the survival rate, as in several studies (Hajian, 2001;Alidina et al, 2004;Shitara et al, 2010;Aghcheli et al, 2011;Ghadimi et al, 2011). The other factor was cigarette smoking which inversely predicted the survival.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Three studies presented results for ESCC and EAC separately [13][14][15][16] and five for ESCC only [17][18][19][20][21]. The remaining four did not differentiate histological type.…”
Section: Resultsmentioning
confidence: 97%
“…The most commonly reported measures were never or ever [16,17,21,23] and never, former, or current [12][13][14][15]22], but nine different category systems were used. Four of the ten ESCC studies [13,[18][19][20] and one of four EAC studies [22] reported at least one smoking category with a statistically significantly increased hazard compared with the never or least smoking category. Figure 2 presents a forest plot of the HRs of pre-diagnosis smoking status (ever versus never, after collapsing categories where necessary) for ESCC and EAC.…”
Section: Tobacco Smokingmentioning
confidence: 99%